O1-S11.06 Burden of genital discharge pathogens and associated characteristics of asymptomatic HIV-infected patients in Johannesburg, South Africa. (10th July 2011) - Lewis, D; Chirwa, T; Msimang, V; Radebe, F; Kamb, M; Sanne, I; Firnhaber, C
Abstract : Background: The prevalence of asymptomatic STIs and urethritis/cervicitis pathogen-associated patient characteristics were determined among patients attending a HIV treatment centre in Johannesburg. Methods: Consenting consecutive HIV-infected patients, asymptomatic for symptoms/signs of genital discharge, were screened over 12 months for gonorrhoea, trichomoniasis, chlamydial and Mycoplasma genitalium infections using a real-time PCR assay. Bacterial vaginosis (BV) and Candida were detected by microscopy (women only). Serological assays diagnosed syphilis (RPR/TPPA) and herpes simplex type 2 (IgG ELISA) infections. Patients returned at 2 weeks; those with positive results were treated and given contact slips for partners. If available, patients' most recent CD4 (83%) and viral load (VL) (60%) results were recorded. Demographic, clinical and behavioural data were collected by nurse-administered questionnaire. A descriptive analysis was conducted to obtain frequency distributions of patient and STI prevalence data. Associations were investigated using the χ 2 test at a 5% level of significance. A multiple logistic regression model was fitted to find factors associated with urethritis/cervicitis pathogens. Results: 1109 patients were enrolled (551 men, 558 women). Compared with men, women were younger with a mean age [SD] of 35.0 [7.3] vs 37.9 [7.9] years (p<0.001), reported more STIs in the past year (65.5% vs 56.5%, p=0.002), were less likely to know their partner's HIV status (53.1% vs 62.3%, p=0.007), were more likely to be on HAART (70.4% vs 59.7%, p<0.001) with an undetectable VL (81.0% vs 69.9%, p<0.001) and a higher mean [SD] CD4 count of 346 [203] vs 232 [173] cells/mm3 (p<0.001). Urethritis/cervicitis pathogens were detected in 119/558 (21.3%) women and 90/550 (16.4%) men (p=0.035). BV and Candida were detected in 155 (28.0%) and 101 (18.3%) women, respectively. Detection of urethritis/cervicitis pathogens was associated with recent sexual intercourse with a regular partner (adjusted OR, aOR 1.64, 95% CI 1.08% to 2.48%). Trichomoniasis was associated with female gender (aOR 2.45, 95% CI 1.39% to 4.32%) and sub-optimal condom use with regular partners (aOR 2.04, 95% CI 1.23% to 3.41%). Conclusions: Urethritis/cervicitis pathogens were highly prevalent among this asymptomatic population. The benefit of introducing such STI screening programmes to improve reproductive health and HIV prevention efforts requires further study.